ORGANIZING SAFE PEDESTRIAN TRAFFIC USING MODERN TECHNOLOGIES - N.I.Otabayev (Western European Studies, 2025)
This article explores the reduction of road traffic accidents involving pedestrians through the implementation of modern technologies. The study analyzes the causes and frequency of pedestrian-related incidents and presents practical recommendations for improving pedestrian safety at intersections, roadways, and urban environments. Special attention is given to the use of intelligent traffic light systems, sensor-based pedestrian detection, and real-time traffic monitoring tools. These solutions are aimed at minimizing risks and enhancing the efficiency of pedestrian traffic management in smart city frameworks.
Keywords: pedestrian; intersection; road